Time-dependent deformation behaviours of two stainless steels at elevated temperature: Correlation between slow strain rate and creep testing - Jinghao Xu; Guocai Chai; Mattias Calmunger (European Journal of Materials, 2024)
Austenitic stainless steels, such as Sanicro 25 and Sanicro 28, exhibit excellent mechanical properties at elevated temperatures. This study investigates their time-dependent deformation behaviours through two distinct testing methods: slow strain rate tensile (SSRT) and creep testing at 650 °C. Microstructural analysis revealed that Sanicro 25 has a finer grain structure and superior high-temperature resistance compared to Sanicro 28. The deformation and facture mechanics have been evaluated. A novel strain energy rate approach was developed to correlate SSRT and creep test data, providing insights into the materials’ high-temperature performance. This study offers a new perspective for evaluating and optimizing stainless steels for demanding applications.